CALCULATION OF THE TEMPERATURE FIELD OF METAL CORRUGATED STRUCTURES OF TRANSPORT FACILITIES WITH CONSIDERATION OF HEAT FLOWS - Luchko Й.; Коvalchuk В. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
A typical transport structure - a small bridge constructed from corrugated metal - serves as the subject for research on temperature distribution. To assess the heat flows affecting prefabricated metal corrugated structures in operational conditions, the research authors conducted multivariate temperature measurements on the surfaces of the metal sheets at different times throughout the year and times of day. These temperature measurements were taken using a thermal imager on a transport facility located on the bypass road of Olesko in Lviv region. The results from the experimental study indicate the temperature distribution on the surface of a metal corrugated sheet under both positive and negative ambient temperatures. The study quantified the heat flows impacting the transport structure made from these metal corrugated sheets in relation to the surrounding environmental temperatures. The research findings revealed that the heat flow absorbed by the metal corrugated structure is unevenly distributed across its surface. Notably, at the "steel-coating" interface, there is a significant difference in heat flow, which could potentially cause damage to the zinc coating. Observations showed that when a zinc coating of 80 microns thickness is applied, variations in the temperature field distribution occur compared to an uncoated surface. The maximum heat flow recorded without the coating was 495.8 W/m², while with the coating applied, it increased to 538.1 W/m². The practical significance of this research lies in the potential application of the measured heat flow values by engineering professionals during the design of transport facilities made from metal corrugated structures, taking into account the effects of thermal loads.